Myelin Basic Protein inhibits the calcium response to phytohaemagglutinin in human lymphocytes. Issue 1 (February 1990) - Bellini, Tiziana; Degani, Diana; Matteuzzi, Maurizio; Dallocchio, Franco
Abstract : Myelin Basic Protein, one of the major membrane protein component of the central nervous system, was used to probe the molecular mechanism of cellular activation by phytohaemagglutinin. Pre-treatment of human lymphocytes with myelin basic protein results in a lower rising of cytosolic concentration of free calcium after stimulation with phytohaemagglutinin. This effect is dependent on myelin basic protein concentration and on the preincubation time of the protein with the cells. It is not due to a interaction between myelin basic protein and phytohaemagglutinin, but appears to be a consequence of the binding of the protein to the cell surface. The reduction of the rise of cytosolic calcium induced by phytohaemagglutinin is specific for the myelin basic protein because other proteins like albumin and protamine have no effect.